보행운동프로그램이 청소년 경직형뇌성마비아동의 자아효능감 및 부모의 양육태도에 미치는 영향 - 사례연구 - 이연섭; Lee Yeonseop; 서동권; Seo Dongkwon; 김경훈; Kim Kyunghun; 이양진; Lee Yangjin (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : The purpose of this study was to investigate the effect of increased gait function enhancement exercise in three adolescent convulsive cerebral palsy sinuses on children's large movement function, balance and gait function, self-efficacy, and guardian attitude. Methods : The purpose of this study was to conduct a program to strengthen trunk muscles and strengthen walking ability 5 times a week for 8 weeks in 3 children with convulsive cerebral palsy in adolescence. The main reinforcement of the program was 20 minutes of muscle strength and 20 minutes of walking on a treadmill five times a week. Exercises were focused on the reinforcement of the flexor muscles of the proprioceptive neuromuscular promotion (PNF) and the extension of the legs in the bridge posture exercise and squat movements. Results : The results of GMFM-88 to determine the effects of this functional enhancement program on the body of children with convulsive cerebral palsy, and PBS & TUG to determine the effects of balance and gait ability were improved. In addition, parenting attitudes of guardians, self-efficacy of children, and self-efficacy of parents increased positively due to mental consequences. Conclusion : The results of GMFM-88 to determine the effects of this functional enhancement program on the body of children with convulsive cerebral palsy, and PBS & TUG to determine the effects of balance and gait ability were improved. In addition, parenting attitudes of guardians, self-efficacy of children, and self-efficacy of parents increased positively due to mental consequences.